EFFECTIVENESS OF DENTAL AND ORAL HEALTH PROMOTION ON IMPROVING KNOWLEDGE AND ATTITUDES OF ELEMENTARY SCHOOL CHILDREN - Riska Nisaul Karimah; Rosihan Adhani; Aulia Azizah; R. Harry Dharmawan Setyawardhana; Nurdiana Dewi (Universitas Lambung Mangkurat, 2025)
ABSTRACTBackground: Caries cases are very high, especially in school children. Data from Riskesdas 2018 showed that the incidence of caries in Banjarmasin was 37.62%. The high number of cases is due to lack of knowledge to maintain dental and oral hygiene. It can affect the learning and achievement of school students. Interventions to increase knowledge are needed as a solution to reduce caries cases in children. One of the educational interventions that can be given is the MOKEGI game application. Purpose: To analyze the effectiveness of health promotion using the MOKEGI educational game on the knowledge and attitudes of dental and oral health of school children. Method: The study used a quasi-experimental design with two group pre and post test. The intervention carried out was MOKEGI (Monopoly of Dental Health) which was carried out for 5 days in the control group and the intervention group. The statistical analysis used was the Wilcoxon and Mann-Whitney tests. Results: The study showed the results of the Wilcoxon attitude test, namely p-value 0.000 (pretest) and 0.248 (posttest). In addition, in the Wilcoxon attitude test, the p-value is 0.000 (pretest) and 0.384 (posttest). The results of the Mann-Whitney test showed a p-value of 0.000 (knowledge) and 0.013 (attitude). Conclusion: there is a significant difference in knowledge and attitudes about dental and oral health between before and after health promotion through the MOKEGI game application. The MOKEGI game application is effective in improving knowledge and attitudes about dental and oral health in school children.Keywords: Attitude, Knowledge, Mouth, Play, Teeth ABSTRAKLatar belakang: Kasus karies sangat tinggi terutama pada anak sekolah. Data Riskesdas 2018 didapatkan angka kejadian karies di Banjarmasin sebesar 37,62%. Tingginya kasus dikarenakan kurangnya pengetahuan untuk menjaga kebersihan gigi dan mulut. Jika hal ini terus terjadi dapat mempengaruhi pembelajaran dan prestasi siswa sekolah. Intervensi untuk meningkatkan pengetahuan sangat diperlukan sebagai solusi menurunkan kasus karies pada anak. Salah satu intervensi edukasi yang dapat diberikan adalah aplikasi permainan MOKEGI. Tujuan: Untuk menganalisis efektifitas promosi kesehatan menggunakan permainan edukasi MOKEGI terhadap pengetahuan dan sikap kesehatan gigi dan mulut anak sekolah. Metode: Penelitian menggunakan desain quasy experiment with two group pre and post test. Intervensi yang dilakukan adalah MOKEGI (Monopoli Kesehatan Gigi) yang dilakukan selama 5 hari pada kelompok kontrol dan kelompok intervensi. Analisis statistic yang digunakan adalah uji Wilcoxon dan Mann-Whitney. Hasil: Penelitian menunjukkan hasil uji Wilcoxon sikap yaitu p-value 0,000 (pretest) dan 0,248 (posttest). Selain itu, pada uji Wilcoxon sikap yaitu p-value 0,000 (pretest) dan 0,384 (posttest). Hasil uji Mann-Whitney menunjukkan p- value 0,000 (pengetahuan) dan 0,013 (sikap). Kesimpulan: terdapat perbedaan signifikan pada pengetahuan dan sikap kesehatan gigi dan mulut antara sebelum dan sesudah promosi kesehatan melalui aplikasi permainan MOKEGI. Aplikasi permainan MOKEGI efektif dalam meningkatkan pengetahuan dan sikap kesehatan gigi dan mulut pada anak sekolah. Kata kunci : Gigi, Mulut, Pengetahuan, Permainan, Sikap.